APPLICATION OF PICTURE AND PICTURE MODELS IN IMPROVING WRITING SKILLS DESCRIPTION CLASS IV STUDENT SUB THEMES THE WORK OF MY PARENTS MI MODERN MUTIARA IMAN KECAMATAN NGUNUT DISTRICT TULUNGAGUNG - Novialita Angga Wiratama (EDU SCIENCES JOURNAL, 2020)
Based on observations during the learning process in Class IV Madrasah Ibtidaiyah (MI) Modern Mutiara Iman students in writing activities, before writing a description of student activities listening to the teacher's explanation about writing a description through writing essays. Then, reading the text in the book, listing and interpreting difficult words with the group after that students with the group write a description essay then exchange the results of work on other groups. Individual students are given homework assigning descriptions with free themes. From the results of student writing there are some errors. From the results of interviews with students obtained data that students have difficulty in pouring ideas into writing. This can be seen in the unorganized writing ideas that will be developed, the suitability of cohesion and low coherence. Students immediately write what is in their minds without making a framework first. Students are less able to develop sentences into coherent paragraphs. There are many errors in the use of punctuation and spelling. This study aims to improve (1) the application of picture and picture models to improve description writing skills in Class IV students at MI Modern Mutiara Iman (2) increase learning outcomes of writing description skills in Class IV students at MI Modern Mutiara Iman. The subjects of this study were Class IV MI Modern Mutiara Iman students in the 2019/2020 school year with a total of 34 students. This type of research is a classroom action research (CAR) with three cycles, including four stages, namely: 1) planning, 2) implementing actions, 3) observations, and 4) reflection. Data collection techniques used in this study include: interviews, observations, tests, questionnaires, documentation, field notes. The results of the research during the process of writing descriptions in each cycle obtained data from 34 students in the first cycle as many as 14 students passed grade the specified scor 70. In the second cycle 26 students passed grade and 31 students passed grade in the third cycle. There are 2 students do not passing grade because they have difficulty writing essay writing so that they need more intensive study guidance compared to their peers.